CONFLICT BETWEEN YUGOSLAVIA AND THE INTERNATIONAL COMMITTEE OF THE RED CROSS IN THE AFTERMATH OF THE SECOND WORLD WAR (Review of Croatian History, 2022)
The International Committee of the Red Cross from Geneva and its activities in the circumstances of the Second World War has been exclusively humanitarian, and the ICRC based it on the then applicable provisions and regulations of the International Law of War (the Law of Armed Conflict). In the aftermath of the Second World War, sporadic allegations began to arise on the ICRC's activities in the war’s circumstances, from 1939 to 1945. These allegations focused in particular on the ICRC's relations with the Authorities of the German Reich, and on the ICRC's activities in favor of the Jews during the war. Initially, the ICRC and its leadership has been facing sporadic accusations from various organizations or individuals, as well as accusations from the Union of Soviet Socialist Republics (USSR), that had no official relations with the ICRC, and shown open hostilities towards the ICRC in the aftermath of the Second World War. In mid-1946, the representatives of Yugoslav authorities accused the ICRC of protecting collaborators and war criminals and further aggravated the situation. The reason for the outbreak of the conflict was the issue of displaced persons, among other. The Yugoslav Red Cross started the conflict that continued through the official Yugoslav press, with the support of the Yugoslav authorities. Soon, both the Yugoslav Red Cross and the Yugoslav authorities extended their allegations towards the ICRC to the entire ICRC’s activities carried out during the war. Based on original archival sources, published sources and literature, the author presents the genesis of the conflict.